Penerjemahan Istilah Ekologi Bahasa Jepang ke Bahasa Indonesia dalam Kumpulan Cerpen Miyazawa Kenji - Elizabeth Ika Hesti Aprilia Nindia Rini; Dewi Kusmiati (IZUMI, 2022)
This paper discusses the translation of Japanese ecological terms into Indonesian. The objective of this research is to describe the technique of translating ecological terms in the source text to the target text and its equivalence. The data in this study was obtained from the collection of short stories Kaze no Matasaburo and Guskobudori no Denki by Miyazawa Kenji as well as its translations in Indonesian by Unpad Press. The data was collected using the literature study method with note-taking techniques. Furthermore, the data were analyzed using the padan method with the basic technique of sorting the determining element (PUP) then continued with the hubung banding technique. The results of data analysis are presented by informal methods. Based on the results of the analysis, translation techniques used in this collection of short stories are, (a) borrowing, (b) calque, (c) transposition, (d) modulation, (e) equivalence, (f) adaptation, (g) borrowing and transposition, (h) modulation and equivalence, and (i) borrowing, transposition, and modulation. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor